Promoting multiple ecosystem services with flower strips and participatory approaches in rice production landscapes - Westphal, Catrin; Vidal, Stefan; Horgan, Finbarr G.; Gurr, Geoff M.; Escalada, Monina; Van Chien, Ho; Tscharntke, Teja; Heong, Kong Luen; Settele, Josef (Elsevier, 2015)
Habitat management needs comprehensive perspectives, considering multiple ecosystem services at local and landscape scales. Stakeholder involvement with participatory research and development programmes for farmers is an essential part of it. Currently, ecological engineering by habitat management and participatory programmes and mass media campaigns are developed to counteract the adverse effects of ongoing intensification of rice production in Southeast Asia. These schemes often suggest the establishment of flower strips. Flower strips are a common measure to promote biodiversity and ecosystem service conservation in industrialised countries, since they aesthetically enrich production landscapes and provide supplementary food resources and shelter for natural enemies and pollinators. We review management options for biological pest control, pollination and cultural services in rice production landscapes and evaluate the parallel development of participatory programmes and mass media campaigns for sustainable rice production. Biological pest control, pollination services and landscape aesthetics could benefit from the establishment of flower strips in rice production landscapes. However, more experimental studies are needed to test the benefits of different plant species, potential interactions between local and landscape scale and interactions between different ecosystem services. Rice farmers should better appreciate their benefits from regulating ecosystem services and should be involved in the development and implementation of ecological engineering. Mass media campaigns and participatory programmes can motivate farmers, but their efficiency needs to be tested in different regions. Combining participatory approaches and mass media campaigns with the establishment of flower strips and other beneficial habitats has potential to increase the sustainability of rice production in Asia.